2019
DOI: 10.1111/ggi.13633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuromuscular electrical stimulation of quadriceps on the quadriceps strength and functional performance in nursing home residents: A comparison of short and long stimulation periods

Abstract: Aim To determine the effect of two neuromuscular electrical stimulation (NMES) periods on quadriceps strength (QS) and functional performance in nursing home residents. Methods A total of 53 older adults living in a nursing home were randomized into two groups: NMES with a short stimulation period and NMES with a long stimulation period. The quadriceps muscles were bilaterally stimulated three times a week for 6 weeks in both groups. Strength was measured with a digital handheld dynamometer and 30‐s chair stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…We found that both training methods improved balance up to 48.9%. This result agrees well with previous find- [43] have used a clinical measure to assess balance, and found that there is 6.0% increase of balance with NMES training of quadriceps muscles. Our finding suggests that, despite the physiological differences in muscle contraction between NMES and VMC, NMES training improves balance similarly to VMC, which rejects our hypothesis that the NMES might change the normal physiology of muscle contraction, leading to change in the balance maintaining strategy while standing.…”
Section: Discussionsupporting
confidence: 93%
“…We found that both training methods improved balance up to 48.9%. This result agrees well with previous find- [43] have used a clinical measure to assess balance, and found that there is 6.0% increase of balance with NMES training of quadriceps muscles. Our finding suggests that, despite the physiological differences in muscle contraction between NMES and VMC, NMES training improves balance similarly to VMC, which rejects our hypothesis that the NMES might change the normal physiology of muscle contraction, leading to change in the balance maintaining strategy while standing.…”
Section: Discussionsupporting
confidence: 93%
“…66 A different study with a physical activity-based intervention in older people in nursing homes also increased the distance covered in a six-minute walking test. 67 Similarly, the same result was achieved in research using yoga intervention in older people in Australia. 68 Weight training has been proven to inhibit decreasing muscle mass and strength due to ageing, improving general health.…”
Section: Discussionsupporting
confidence: 58%
“…Physical exercise is considered one of the most effective strategy to slow down muscle aging, especially in terms of mass and function (Negaresh et al, 2019). Besides the classic training, NMES is also a valid method that enhances muscle performance and structure (Acaröz Candan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%